2016
DOI: 10.1103/physrevb.93.155404
|View full text |Cite
|
Sign up to set email alerts
|

Quantization of entropy in a quasi-two-dimensional electron gas

Abstract: We demonstrate that the partial entropy of a two-dimensional electron gas (2DEG) exhibits quantized peaks at resonances between the chemical potential and electron levels of size quantization. In the limit of no scattering, the peaks depend only on the subband quantization number and are independent on material parameters, shape of the confining potential, electron effective mass and temperature. The quantization of partial entropy is a signature of a topological phase transition in a 2DEG. In the presence of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
33
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 12 publications
3
33
0
8
Order By: Relevance
“…This transition is a particular case of the Lifshitz topological transition [13]. It has been recently demonstrated that such transformations are accompanied by the spikes in the entropy per particle as well as by the spikes in the temperature derivative of the chemical potential of the electron or hole gas [14]. Below we show that the magnetic susceptibility of the system experiences similar spikes in the vicinity of the Lifshitz transition points.…”
supporting
confidence: 56%
See 1 more Smart Citation
“…This transition is a particular case of the Lifshitz topological transition [13]. It has been recently demonstrated that such transformations are accompanied by the spikes in the entropy per particle as well as by the spikes in the temperature derivative of the chemical potential of the electron or hole gas [14]. Below we show that the magnetic susceptibility of the system experiences similar spikes in the vicinity of the Lifshitz transition points.…”
supporting
confidence: 56%
“…Before presenting the numerical results, let us focus on the simplified analytical model which takes into account only one type of holes but provides a clear physical picture of the effect of topological Lifshitz transitions on the hole spin susceptibility and the ferromagnetic order of Mn spins. Let us represent the density of heavy-hole states as g(E) = (m * /π 2 ) ν Θ(E − E hhν ), where m * is the heavy-hole effective mass, E hhν are the energies of the size-quantized subbands, and Θ(E) is the Heaviside step function [14,15]. Furthermore, let us assume that relevant temperatures are low enough so that the thermal broadening in Eq.…”
mentioning
confidence: 99%
“…Near the Lifshitz transition points, µ = ±∆, we observe that the dependences s(µ) are monotonic functions, so that these points are not marked by spikes. This is typical for any system where DOS has just one discontinuity [17]. Nevertheless, the entropy per particle quantization rule for graphene s(µ = ±∆) = ±2 ln 2 ЖЭТФ is fulfilled.…”
Section: жэтфmentioning
confidence: 96%
“…It was theoretically predicted [4] that in a quasi-twodimensional electron gas (2DEG) with parabolic dispersion, the entropy per electron exhibits quantized peaks when the chemical potential crosses the size quantized levels. The amplitude of such peaks in the absence of scattering depends only on the subband quantization number and is independent of material parameters, shape of the confining potential, electron effective mass, and temperature.…”
Section: Introductionmentioning
confidence: 99%